Aceh as a Model of Halal Trade in Financial Goods and Services Regulation based on Pancasila within the Framework of National Law in Indonesia - Yani, Teuku Ahmad; Abdurrahman, Abdurrahman; Mulyana, Ida (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
The province of Aceh holds a special autonomy status, which allows Aceh to possess the jurisdiction to enforce the Islamic law specifically in the realm of the civil law, particularly in matters related to commerce. In Aceh, trading in commodities and financial services must adhere to the principles of the Islamic law, ensuring that only halal goods are involved. Using the Content Analysis Techique, this study adopts a combined approach of the national law and the Islamic law. The data was gathered by literature and document analysis, including an examination of legal statutes, scholarly publications, and relevant books pertaining to the topic being discussed. This study asserts that the trading of halal commodities and financial services are fundamental aspects of the Islamic law, a concept that is unfamiliar in legal frameworks rooted in the Western civil law systems. Consuming food that is not halal and engaging in usury are both forbidden under the Islamic law. Within the framework of sharia, commerce is not just confined to individuals, but can also be subject to public scrutiny if they contravene fiqh, so rendering them impermissible. In order to achieve this legislative objective, the Aceh Province established a regulatory framework in the form of the Aceh Qanun, in line with the authority granted by Article 125 of Law Number 11 of 2006. This model has facilitated the emergence of a trade system that is devoid of any forbidden aspects, and financial services that are free from the practice of charging excessive interest, in accordance with Sharia principles. As a result, it differs from the conventional practices of trading goods and services that are prevalent within Indonesia. It is important to highlight that both Pancasila and National law ensure the freedom of citizens' rights to practice the Islamic law, including engaging in halal trade of commodities and financial services.